Parole e forme della devozione: Cristina di Francia, duchessa di Savoia, e il “regio sacello” di San Salvario a Torino - Beltramini, Maria (Opus Incertum, 2022)
The essay discusses the early history of the San Salvario chapel in Turin, commissioned by Christine of France – Duchess of Savoy and widow of Victor Amadeus I – as a votive offering for obtaining the right to govern the State until the full age of her heir. Guided by the inscription on the façade, the essay reconstructs the primitive design of the church (later heavily transformed), clarifies its reasons, meanings and functions, questions the critical interpretations to date and proposes a new stylistic assessment.